Freeze-dried snake antivenoms formulated with sorbitol, sucrose or mannitol: Comparison of their stability in an accelerated test - Herrera Vega, María (2014)
Freeze-drying is used to improve the long term stability of pharmaceutical proteins. Sugars and polyols have been successfully used in the stabilization of proteins. However, their use in the development of freeze-dried antivenoms has not been documented. In this work, whole IgG snake antivenom, purified from equine plasma, was formulated with different concentrations of sorbitol, sucrose or mannitol. The glass transition temperatures of frozen formulations, determined by Differential Scanning Calorimetry (DSC), ranged between −13.5 °C and −41 °C. In order to evaluate the effectiveness of the different stabilizers, the freeze-dried samples were subjected to an accelerated stability test at 40 ± 2 °C and 75 ± 5% relative humidity. After six months of storage at 40 °C, all the formulations presented the same residual humidity, but significant differences were observed in turbidity, reconstitution time and electrophoretic pattern. Moreover, all formulations, except antivenoms freeze-dried with mannitol, exhibited the same potency for the neutralization of lethal effect of Bothrops asper venom. The 5% (w:v) sucrose formulation exhibited the best stability among the samples tested, while mannitol and sorbitol formulations turned brown. These results suggest that sucrose is a better stabilizer than mannitol and sorbitol in the formulation of freeze-dried antivenoms under the studied conditions.